Dose-Response Curves in Chemical Carcinogenesis - William J. Waddell (SAGE Publishing, 2004)
Extrapolation from studies of chemical carcinogenicity in rodents, at high doses, to humans, at the typically low doses to which we are exposed, has been one of the most controversial issues in toxicology. Many chemical carcinogenesis experiments currently are evaluated on a linear scale for dose. Log dose has been the standard for decades in pharmacology and toxicology for noncancer toxicities and there is no reason to think that it should not apply to chemical carcinogenesis. Furthermore, log dose is consistent with fundamental principles of chemistry. Direct comparisons of linear and logarithmic scales for dose illustrate the deceptive nature of linear plots for dose; low doses, which is where our interest lies in comparing human exposures, are compressed beyond evaluation by a linear scale. Unequivocal thresholds for carcinogenicity are shown when the dose-response curves for animal studies done at high doses are evaluated on a log scale for dose. This observation now raises the issue of the relevance to human exposures of these high-dose experiments in animals. Studies analyzed by this log dose to linear response procedure demonstrate that the thresholds from animal experiments can be used to calculate safety factors for human exposure and that humans are more resistant than animals to carcinogenesis from chemicals.